Functional organic dyes for health‐related applications. Issue 4 (30th July 2020) - Cheng, Wenyu; Chen, Hongtao; Liu, Chang; Ji, Chendong; Ma, Guiping; Yin, Meizhen
Abstract: Nowadays, photo‐based diagnosis and treatment techniques have been the focus in health‐related fields. Organic dyes with delicately designed structures and tunable optical properties were used for fluorescence and photoacoustic imaging as well as phototherapy including photodynamic and photothermal therapy. The theranostic agents exhibit better treatment efficacy with minimized invasiveness, which have shown great potential for disease treatment. To suit health‐related application, regulating the photophysical properties of functional organic dyes and improving their biocompatibility is the prerequisite for designing efficient optical diagnostic reagents. This review summarizes recent advances in the design, fabrication, and applications of functional organic dye‐based material in health‐related fields. The design and preparation strategies of these dyes mainly include tuning the absorption, emission, photodynamic and photothermal properties of dyes through chemical modification of chromophore scaffold, obtaining water‐soluble macromolecules through peripheral functional modification, constructing nanotheranostic reagents through self‐assembly process or preparing fluorescent detection devices. Based on these materials, functional organic dyes have been used in a variety of cancer treatment methods for bacterial detection and antibacterial fields, in vitro and in vivo disease detection, as well as fluorescence/photoacoustic imaging‐guided cancer therapy, which were summarized in this review. Finally, possible functionalization directions of organic dyes are also proposed to meet the needs of advanced health‐related applications. Abstract : The design, fabrication, and applications of functional organic dye‐based material in health‐related fields is summarized. Main content includes preparing fluorescent/photodynamic/photothermal systems and their applications in bacterial detection and antibacterial fields, in vitro and in vivo disease detection, as well as fluorescence/photoacoustic imaging‐guided cancer therapy.